Proteomics analysis of the Francisella tularensis LVS response to iron restriction: induction of the F. tularensis pathogenicity island proteins IglABC - Lenco, Juraj; Hubálek, Martin; Larsson, Pär; Fucíková, Alena; Brychta, Martin; Macela, Ales; Stulík, Jirí (FEMS microbiology letters, 2007)
Francisella tularensis is a highly virulent, facultative intracellular pathogen that causes tularemia in humans and animals. Although it is one of the most infectious bacterial pathogens, little is known about its virulence mechanisms. In this study, the response of F. tularensis live vaccine strain to iron depletion, which simulates the environment within the host, was investigated. In order to detect alterations in protein synthesis, metabolic labeling, followed by 2D-PAGE analysis was used. Globally, 141 protein spots were detected whose levels were significantly altered in the iron-restricted medium. About 65% of the spots were successfully identified using mass spectrometric approaches. Importantly, among the proteins produced at an increased level during iron-limited growth, three proteins were found encoded by the igl operon, located in the F. tularensis pathogenicity island I (FPI). Of these, the IglC and IglA proteins were previously reported to be necessary for full virulence of F. tularensis. These results, obtained at the proteome level, support and confirm recently published data showing that the igl operon genes are transcribed in response to iron limitation.
Keywords: operon; Virulence Factors; Gene Expression Profiling; proteomika; Gene Expression Regulation, Bacterial; Electrophoresis, Gel, Two-Dimensional; Francisella tularensis; železo; Mass Spectrometry; Operon; Bacterial Proteins; Iron; Proteomics; genomové ostrovy; Genomic Islands; 2D gelová elektroforéza; regulace genové exprese u bakterií; stanovení celkové genové exprese; faktory virulence; bakteriální proteiny; hmotnostní spektrometrie